Gastronomic Branding: New ‘Menu’ for Tourism, Diplomacy, and Destination Branding - Niken Febrina Emungtyas (Jobmark: Journal of Branding and Marketing Communication, 2020)
Gastronomic branding has become a popular strategy today as a consequence of the development of tourism branding, destination branding, and soft/cultural diplomacy. This article examines the content and ideas of a book entitled Gastronomi (Brand): Konsep dan Gagasan Awal written by Irwansyah, a researcher from the University of Indonesia. As an initial idea (according to the term used by the author), this book provides adequate insight into gastronomy in the Indonesian context. Although, of course, it requires a more comprehensive discussion to get to the technical or strategic level so that it can be easily applied by industry players, professionals, and government as part of, both destination and tourism branding efforts and soft/cultural diplomacy.